A Review of Orthodontic Indices - Gupta, Alka; Shrestha, Rabindra Man (Orthodontic Journal of Nepal, 2014)
Orthodontic indices are essential component in assessing severity, complexity and treatment outcome of malocclusion. Moreover, they are useful in evaluating treatment need, funding for treatment cost and public health aspects of orthodontic treatment. The present article reviews orthodontic indices used for clinical and epidemiologic purposes. The article attempts to classify the indices in qualitative and quantitative methods